Wild edible fruits generate substantial income for local people of the Gunung Leuser National Park, Aceh Tamiang Region - Suwardi, Adi Bejo; Navia, Zidni Ilman; Harmawan, Tisna; Syamsuardi, Syamsuardi; Mukhtar, Erizal (Ethnobotany Research and Applications, 2020)
Background: Gunung Leuser National Park offers a variety of wild edible fruit species (WEFs) with food, nutrition, medicine, and economic value to the local people. In recent times, these WEFs have been threatened by over-exploitation, land-use changes, and biodiversity loss. This study aims to investigate the diversity of WEFs and their contribution to household income for communities living around the National Park. Methods: The study was conducted in three sub-districts adjacent to Gunung Leuser National Park. The plant materials were randomly collected from three sub-districts, while local knowledge was gathered through a structured survey and in-depth interviews. The informant sample comprised 450 people, 150 from each of the three sub-districts. Results: A total of 54 wild edible fruit plants belonging to 41 genera and 27 families were recorded in the study area. Thirty-nine (72.22 %) species were found growing in forests, 12 (22.22 %) species in farmland, and 3 (5.56%) species occur in the bush. Several species have economic value including Baccaurea macrophylla (Müll.Arg.) Müll.Arg., Baccaurea polyneura Hook.f., Diospyros kaki L.f., Flacourtia rukam Zoll.&Moritzi, Garcinia atroviridis Griff. ex T.Anderson, Garcinia xanthochymus Hook.f. ex T.Anderson, Lansium domesticum Corrêa, Mangifera foetida Lour., Mangifera odorata Griff., Mangifera laurina Blume, Nephelium cuspidatum Blume, Passiflora edulis Sims., Pometia pinnata J.R. Forst. & G. Forst., Syzygium aqueum (Burm. f.) Alston, and Syzygium malaccense (L.) Merr. & L.M. Perry. These fruits formed a source of household income and were harvested by approximately 82% of respondents. The sale of WEFs contributed approximately 34.31% of the total annual household income. These findings confirm the assumption that WEFs are important for the generation of household income. Conclusions: This study demonstrates the importance of WEFs to local communities in Aceh Tamiang, Indonesia, particularly rural communities living near Gunung Palung National Park. WEFs play an important role in rural livelihoods by ensuring food, medicine, and sustained income. Policies and legislation involving stakeholders are required to ensure the cultivation, management, sustainable use, and promotion of WEFs in order to encourage the economic growth of the rural community in the Aceh Tamiang region.